TEACHING SPEAKING ON PROCEDURE TEXT BY USING MEDIA FLASH ANIMATION - Nurhuda, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research intended to know how effective the use media flash animation in teaching speaking on procedure text is for the ninth grade students of SMPN 1 Terentang. The research method used was pre experimental research. The population of this research was all of the ninth students of SMPN 1 Terentang in academic year 2015/2016. The sample was class A which consists of 27 students. The technique of data collection was the measurement technique and the tool used was test. The researcher analyzed the data by using t-test. The result showed that there was significant difference on students’ speaking. It showed that was higher than and the criteria effect size was categorized as high effect. As a result, the null hypothesis (was rejected and the alternative hypothesis ( was accepted with the criteria effect was high. Hence, it was inferred that there was significant difference between students’ achievement before being taught by media flash animation and after being taught by media flash animation. In other word, teaching by using media flash animation affects significantly in the students’ speaking on procedure text. Key words: teaching speaking, media flash animation, pre experimental Abstrak: penelitian ini bertujuan untuk mengetahui seberapa efektif mengajar berbicara pada teks prosedure menggunakan media animasi flash pada siswa kelas sembilan SMPN 1 Terentang. Metode penelitian yang digunakan adalah pre experimental. Populasi pada penelitian ini adalah seluruh siswa kelas sembilan SMPN 1 Terentang tahun ajaran 2015/2016. Samplenya adalah siswa kelas A yang berjumlah 27 siswa. Teknik pengumpulan data yang digunakan adalah teknik penilaian dan alat yang digunakan adalah test. Peneliti menganalis data menggunakan t-test. Data menunjukkan bahwa lebih tinggi dibanding dan kriteria dari keeffektifannya adalah dikategorikan sebagai keefektifan yang tinggi. Sebagai hasilnya, null hypothesis ditolak dan alternative hypothesis diterima dengan kategori kriteria yang tinggi. Oleh karena itu, dapat disimpulkan bahwa terdapat perbedaan yang siknifikan antara mengajar berbicara pada prosedur teks sebelum dan sesudah menggunakan media animasi flash. Dengan kata lain, mengajar menggunakan media animasi flash mempengaruhi secara signifikan terhadap berbicara siswa pada teks prosedur. Kata kunci: mengajar berbicara, media animasi flash, pre-eksperimental